Superconducting properties of In doped ZrNi2Ga1−xInx. (April 2019) - Reigle, Alex; Mason, Kelly; Slattery, Jessica; Lee, Scott; Jamison, Tyler; Eggert, Adam; Vincely, Vinoin; Wong, Darren; Guo, Yuliang; Brock, Jeffrey; Khan, Mahmud
Abstract: We report on the effect of In doping on the superconducting properties of ZrNi2 Ga1− x In x ( x = 0.0.05, 0.10, 0.15) Heusler alloys. While the samples with x < 0.1 exhibited the single phase, cubic L21 structure, small concentrations of ZrGa2 -type orthorhombic secondary phases formed on the samples with x ≥ 0.1. Electrical resistivity and dc magnetization measurements showed that the superconducting transition temperature of the compounds decreased with increasing In concentration. All samples showed paramagnetic ordering above their respective superconducting transition temperature. The observations suggest that for x ∼0.45 the ZrNi2 Ga1− x In x compound might exhibit a quantum phase transition. Highlights: The superconducting properties of ZrNi2 Ga1− x In x have been investigated. The superconducting transition temperature decreases with increasing In concentration. A quantum phase transition may occur in the system for x ∼0.45.